Causes and risk factors of deaths in maintenance hemodialysis patients with end-stage renal disease - ZHOU Kang-kang; ZHANG Jun-yu; ZHOU Hong-wei (Linchuang shenzangbing zazhi)
Objective To analyze the causes of deaths in maintenance hemodialysis patients and to explore the risk factors associated with deaths. M ethods A retrospective analysis was performed on 2 6 8 maintenance hemodialysis cases admitted at the Blood Purification Center of the First Affiliated Hospital of Guangxi Medical University from Jan. 2 0 1 2 to Jan. 2 0 1 7. 2 0 2 survivors served as control group,and 6 6 deaths as case group. The clinical indicators were compared. Results In the case group,there were 2 1 cases( 3 1. 8 %) of cardiovascular diseases,1 6 cases( 2 4. 2 %) of cerebrovascular diseases, 1 5 cases( 2 2. 7 %) of infection, 5 cases( 7. 6%) of gastrointestinal bleeding,2 cases( 3%) of hyperkalemia,7 cases( 10. 6%) of unknown causes. The dialysis time was significantly shorter,and albumin,hemoglobin,hematocrit,magnesium,uric acid and serum creatinine were significantly lowerin the case group than those in the control group. The dialysis starting age was significantly older,and the percentage of neutrophils,neutrophilto lymphocyteratio,cardiothoracic ratio were significantly higher in the case group than those in the control group( P < 0. 0 5). Binary logistic regression analysis showed that the advanced age,malnutrition,anemia,inflammation,low magnesium,low uric acid,low creatinine,and high neutrophilto lymphocyteratio and high cardiothoracic ratio were the risk factors for deaths. Conclusions The causes of deaths in maintenance hemodialysis patients mainly include cardiovascular and cerebrovascular diseases,infections,etc. The advanced age,malnutri-tion,anemia,inflammation,low magnesium,low uric acid,low creatinine,high neutrophilto lymphocyteratio and high cardiothoracic ratio were the risk factors for deaths in maintenance hemodialysis patients.